Penentuan Kadar Flavonoid Daun Rumput Knop (Hyptis capitata Jacq.) Menggunakan Spektrofotometri UV-Vis - Hamsidar Hasan; A. Mu'thi Andy Suryadi; Ni Luh Widiastuti; Syamsul Bahri (State University of Gorontalo, 2023)
Knop grass (Hyptis capitata Jacq.) is a weed used as a tradisional medicine, especially for the leaves. Flavonoids are one of the secondary metabolites contained in the Knop Grass (Hyptis capitata Jacq.) leaves, wich function as anti-inflammatory, analgesic, antipyretic and anti-diabetic. The amount of extracted flavonoids is optimized by choosing the right extraction method, as it will determine the amount of substance that can be attracted and obtain a high content of active substansces. This research aimed to compare the flavonoid levels in the methanol extract of Knop Grass (Hyptis capitata Jacq.) leaves in two different maceration methods: multilevel maceration and total maceration. Multilevel maceration employed n-hekxane, ethyl acetat and methanol solvents, while total maceration employed methanol solvent. In the meantime, the qualitative analysis in this reaserch used the color reagent test method, whereas the thin layer chromatography used the eluent, namely n-hexane : ethyl acetate with a ratio (7:3). In addition, the quantitative analysis used the UV-Vis spectrophotometry method at a maximum wavelength of 435 nm with standard quercetin as a comparison. The result signified that the average flavonoid level in the methanol extract of Knop Grass (Hyptis capitata Jacq.) leaves using the multilevel maceration method was 2,9750%. The total maceration method was 4,8822%. Furthermore, the total maceration method donated the highest concentration obtained from the methanol extract of Knop Grass (Hyptis capitata Jacq.) leaves.